Digital Transformation and Conflict Management in the Society 5.0 Era: A Bibliometric Review of Islamic Educational Institutions in Indonesia - Rifa'i Rifa'i; Aniq Nauval Huda; Moh Alfarobi; Ahmad Rafi Muzadi; Laily Hidayati (Al-Hikmah: International Journal of Islamic Studies, 2026)
This study aims to map and analyze research trends on digital transformation and conflict management in Indonesian Islamic educational institutions in the context of the Society 5.0 era using a bibliometric review approach. Data from Scopus-indexed documents were analyzed using co-citation and bibliographic coupling techniques through VOSviewer to map the intellectual structure and research trends of digital transformation in Islamic education. The research methodology followed the PRISMA 2020 protocol by analyzing publications from Scopus and SINTA databases, with bibliometric visualization performed using VOSviewer 1.6.20 software and Biblioshiny. The results showed that Indonesia is the dominant contributor with 323 publications (65.4%), followed by Malaysia, with publication output increasing significantly since 2020, correlating with the global COVID-19 pandemic. The findings identified seven main thematic clusters encompassing the urban-rural digital divide, convergence of pedagogical and technological frameworks, and the critical roles of leadership, self-efficacy, and educational resilience. Additionally, a "Hybrid Resilience" paradigm emerged, where Pesantren and Madrasah integrate moderate theology (Wasathiyah), revitalization of local wisdom-based social capital, and adoption of global values such as Sustainable Development Goals (SDGs). The research results indicate that conflict management is crucial in Islamic educational institutions, where conflict is unavoidable and conflict control is essential to achieve institutional goals. The study also reveals growing integration of Artificial Intelligence tools, including ChatGPT and digital Al-Quran applications, which enhance student learning motivation and critical thinking. The implications of this research provide strategic guidance for policymakers, educators, and researchers in formulating an inclusive and effective digital future for Islamic education globally.